Implementasi Metode Naive Bayes pada Sistem Stop Kontak untuk Klasifikasi Perangkat Elektronik dalam Kamar - Shelsa Faiqotul Himmah; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
An electric socket is a tool that becomes one of the basic needs of each individual. Serves as in-between of power source with an electronic socket device has not changed in terms of function or appearance. Along with the development of electronic devices or so-called smart devices, electric socket is does not get special attention in the development of functions. Therefore we made a breakthrough on the function of the electric socket to make a classification on electronic devices embedded in the electric socket. Because of the many types of electronic devices available then the use of electronic devices is limited only to electronic devices in the room that is; hairdryer, phone charger, laptop charger, iron, and fan. The process of making a classification system using current sensor YHDC SCT-013-020 as a current reader. Then the current value will be processed by NodeMCU v1.0 and naive bayes as the method used to classify. Classification data will be stored on cloud storage that can be accessed through android smartphone. The experiment was done by making 3 combinations of 5 electronic devices so there are 10 combinations. Based on the test obtained percentage of 83.33% of the system can classify the device that is in use and requires an average time for 206340.6 ms to perform data acquisition and average time for 6.3 ms to do classification.